Migrant entrepreneurs and firm innovation. (11th August 2021) - Gao, Jie; Wu, Huiying; You, Jiaxing; Smith, Meg
Abstract: This study examines the impact of entrepreneurs' migrant background on firm innovation as measured by spending on research and development and by the number of patents. We find that entrepreneurs' migrant background is positively related to firm innovation level, and that this relation is weakened by a less supportive environment. We also find that migrant entrepreneurs have a higher propensity to take risks than their local peers. Further analyses show that the relationship between migrant background and innovation varies in times of uncertainty and that entrepreneurs' migrant background is positively associated with innovation quality, innovation efficiency and firm performance.